2014
DOI: 10.1091/mbc.e14-03-0818
|View full text |Cite
|
Sign up to set email alerts
|

A1adenosine receptor–stimulated exocytosis in bladder umbrella cells requires phosphorylation of ADAM17 Ser-811 and EGF receptor transactivation

Abstract: The role of phosphorylation in ADAM17-dependent shedding is controversial. We show that the A1 adenosine receptor stimulates exocytosis in umbrella cells by a pathway that requires phosphorylation of ADAM17–Ser-811, followed by HB-EGF shedding and EGF receptor transactivation. Preventing ADAM17 phosphorylation blocks these downstream events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…The cytoplasmic tail of ADAM proteases is discussed to regulate catalytic activity of some family members (Figure 1c). It contains several sites that can be phosphorylated by diverse cytoplasmic kinases such as protein kinase C (PKC) [22,23], extracellular regulated kinase (ERK) [24,25], and p38 [26]. In particular, engagement of G-protein coupled receptors (GPCRs) that are coupled to an αq/11 subunit results in the downstream activation of phospholipase C (PLC), an increase in the second messengers diacylglycerol (DAG), inositol triphosphate (IP3), and Ca 2+ , and subsequent activation of PKCs [27,28,29].…”
Section: Adam Proteasesmentioning
confidence: 99%
“…The cytoplasmic tail of ADAM proteases is discussed to regulate catalytic activity of some family members (Figure 1c). It contains several sites that can be phosphorylated by diverse cytoplasmic kinases such as protein kinase C (PKC) [22,23], extracellular regulated kinase (ERK) [24,25], and p38 [26]. In particular, engagement of G-protein coupled receptors (GPCRs) that are coupled to an αq/11 subunit results in the downstream activation of phospholipase C (PLC), an increase in the second messengers diacylglycerol (DAG), inositol triphosphate (IP3), and Ca 2+ , and subsequent activation of PKCs [27,28,29].…”
Section: Adam Proteasesmentioning
confidence: 99%
“…Since GPCRs are able to transactivate EGFR through pro-ligand shedding, mediated by ADAM and MMP family [ 13 15 ], and, on the other hand, TGF-alpha, an EGFR ligand, is able to induce REG4 expression through SP1 activation. It seems that a positive feedback loop may exist in gastric cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…The interesting part of REG4 is that it is able to activate EGFR pathway, in the meantime, REG4 mRNA can be induced by some EGFR ligands, [ 12 ] which suggests that a positive feedback loop of REG4 regulation is likely to exist in cancer tissues. While REG4′s interactive partner has not been identified so far, there are quite a few proofs that many G-protein coupled receptors are capable of transactivating EGFR through a disintegrin and metalloproteinase (ADAM) or matrix metalloproteinase (MMP) family, which cleaves the pro-ligands of EGFR [ 13 15 ]. In addition, several transcription factors downstream of EGFR are closely associated to poor outcome of gastric cancer patients [ 16 , 17 ], which might contribute to REG4 inducement after EGFR ligands stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…These ecto-enzymes can be secreted or membrane-bound and act to degrade (ATP and UTP) to respective nucleotides, including conversion into adenosine, which activates its own class of P1 receptors also expressed within the urothelium. Studies have also shown that activation of P1 (adenosine) receptors within the urothelium may modulate umbrella-cell exocytosis (34). Thus, alterations in membrane turnover cannot only increase apical surface area (as described above), but also regulate the number and function of receptors and channels at the cell surface and participate in release of a variety of mediators.…”
Section: Urothelial-cell Interactionsmentioning
confidence: 99%
“…This process of ongoing replacement of apical membrane by newly fused discoid vesicles also serves to maintain the urothelial barrier. There is evidence that this stretch-induced exocytosis is dependent on activation of epidermal growth-factor receptor (EGFR) (34). These processes allow the bladder to accommodate increasing volumes of urine during filling without compromising the barrier function.…”
Section: Urothelial Barrier Functionmentioning
confidence: 99%